Dwarf Detachment and Globular Cluster Formation in Arp 305 - Hancock, M; Smith, B. J; Struck, C; Giroux, M. L; Hurlock, S (2009)
Tidal Dwarf Galaxies (TDG), concentrations of interstellar gas and stars in the tidal features of interacting galaxies, have been the subject of much scrutiny. The `smoking gun' that will prove the TDG hypothesis is the discovery of independent dwarf galaxies that are detached from other galaxies, but have clear tidal histories. As part of a search for TDGs we are using GALEX to conduct a large UV imaging survey of interacting galaxies selected from the Arp Atlas. As part of that study, we present a GALEX UV and SDSS and SARA optical study of the gas-rich interacting galaxy pair Arp 305. The GALEX UV data reveal much extended diffuse UV emission and star formation outside the disks including a candidate TDG between the two galaxies. We have used a smooth particle hydrodynamics code to model the interaction and determine the fate of the candidate TDG.